Hukum Islam dan Patronase dalam Penentuan 1 Ramadhan di Bungong Keumang - Cut Rahma Rizky; Agus Nurhadi (Al-Ahkam, 2018)
In 2017, people in Bungong Keumang village started fasting on Thursday, and they did not follow the government's decision to start fasting on Saturday. They prefer to follow the decisions of religious leaders who often overtake fasting, up to 2-3 days. This difference with the government has been going on for a long time, and almost every year has happened. This paper answers the question of why people in Bungong Keumang prefer to follow the decisions of religious leaders in starting Ramadhan fasting rather than following government decision? With in-depth interviews, answers were obtained that the choice of the community was more due to longstanding social patronage relations based on the exchange of values between religious leaders (patrons) and worshipers (clients) that are mutually beneficial to each other. The determination of 1 Ramadhan which is an area of Islamic law is an 'important arena' to strengthen patronage relations. However, at present the client's obedience to patrons is also shifting. The community is increasingly rational in making choices, access to information is also getting easier, and power relations are also decreasing, so the determination of 1 Ramadhan will become stronger into the area of astronomy and Islamic law.